PERMINTAAN MAAF DALAM BAHASA BANJAR: KAJIAN PRAGMATIK - NFN Jahdiah (Balai Bahasa Sulawesi Tengah, 2016)
This study aims to describe apology in Banjar language base on pragmatics study.Pragmatic shows us the principles of using language for interaction. Analysis throughpragmatic is a study about the ability using language to choose sentence according tothe context. The method used in this study is qualitative. The main data are utterancesthat contain apologize expresses in daily life in banjar informal situation. The dataare gained through taking note, recording, and interviewing. The result shows that theexpression of apologize of the speaker to say it directly are maaflah ‘I am sorry,jangan sariklah ‘do not be angry’, and ampun banarlah ‘I am terribly sorry’.